2015
DOI: 10.1016/j.jbspin.2014.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Quickly progressive amyotrophy of the thigh: An unusual cause of rapid chondrolysis of the knee

Abstract: While rapidly destructive OA is more recognized in hip, we report the case of a 50-year-old woman who presented a rapid chondrolysis in the patellofemoral joint in a context of rapid loss of muscular strength. She had arthralgia, myalgia and proximal muscular deficit of the limbs. Creatine phospho kinase level was elevated and electromyogram exam showed a myogenic syndrome. Neither immune nor visceral disease was highlighted. As we suspected a polymyositis, we started corticosteroids and physiotherapy, then me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…However, whether these findings are attributable to the presence of either pre existing muscle pathology and /or an alteration in afferent input to the central nervous system and long term adaptations that may prove detrimental to articular cartilage in vulnerable joints such as the knee is impossible to establish. Although Ferrari, et al [50] found concomitantly worsening of the muscular deficit and atrophy of hamstrings led to persistent and disabling knee pain associated with osteoarthritic joint damage, in a patient with progressive amyotrophy, whether this occurs in osteoarthritis cases more generally over time is also not known.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…However, whether these findings are attributable to the presence of either pre existing muscle pathology and /or an alteration in afferent input to the central nervous system and long term adaptations that may prove detrimental to articular cartilage in vulnerable joints such as the knee is impossible to establish. Although Ferrari, et al [50] found concomitantly worsening of the muscular deficit and atrophy of hamstrings led to persistent and disabling knee pain associated with osteoarthritic joint damage, in a patient with progressive amyotrophy, whether this occurs in osteoarthritis cases more generally over time is also not known.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…Articular cartilage injury does not heal instantly, unfortunately, and the methods for articular cartilage repair are few. Slight cartilage damage can be treated by strengthening the surrounding muscles by physiotherapy, and pain and swelling can be reduced by anti-inflammatory drugs [30][31][32]. However, if the cartilage injury is more serious, surgical treatment may be considered.…”
Section: Different Treatments For Articular Cartilage Damage (Healingmentioning
confidence: 99%
“…In addition, with age, the pore area at the surface of the bone, such as the femur, is known to increase [36], decreasing the overall fracture strength and increasing the susceptibility for the cartilage to wear. Other causes of articular cartilage damage include infections and diseases such as septic arthritis [37,38] and myopathy [39]. …”
Section: Causes Of Cartilage Damagementioning
confidence: 99%
“…It is important that whichever treatment is used, the joint must maintain the freedom of movement that would be expected [40]. When the cartilage damage or arthritis is mild, physiotherapy can be used to strengthen the surrounding muscles, in conjunction with anti-inflammatory drugs to reduce pain and swelling [39,41,42]. Regular exercise has also been observed to control mild symptoms [43].…”
Section: Current Strategies For Cartilage Defect Repairmentioning
confidence: 99%